Pengaruh Literasi Digital Terhadap Prestasi Belajar Pada Siswa SMP Pusaka Bangsa Karawang - Dewamas Krisna Yudha; Irawan Irawan; Diana Khuntari (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2023)
Advances in information technology have ushered in a new era of digital world. With digital developments, students have new ways of finding information through digital media. This certainly helps students meet their information needs more practically, effectively, and efficiently. Students at SMP (Middle School) Pusaka Bangsa in Karawang have also experienced the impact of this development. The school is located in an urban area where technology is widely accessible. In addition, the students of this school have an average grade of 88 and have won various competitions in the academic field. This study aims to determine the effect of digital literacy on student achievement at SMP Pusaka Bangsa Karawang. Aspects of digital literacy include: technology, cognitive, and ethics. While aspects of learning achievement include: affective, cognitive, and psychomotor. The research method used is quantitative by collecting data through questionnaires. This study examined a sample of 95 respondents who were students of SMP Pusaka Bangsa Karawang. The data collection method in this study used population research techniques by distributing questionnaires online in the form of Google Forms. The data obtained were then processed using SPSS version 26 software with instrument tests (validity and reliability tests), classical assumption tests (in the form of normality tests, linearity tests, and heteroscedasticity tests), and hypothesis testing (simple linear regression tests, R2 tests, and Q). The results of the study show that digital literacy has an influence of 27% on student achievement at Pusaka Bangsa Karawang Middle School; the remaining 73% is caused by other variables outside the scope of this study. Suggestions were given to the school to improve students' digital literacy in the cognitive aspect and student achievement in the psychomotor aspect.